Exogenous Melatonin Suppresses Dark-Induced Leaf Senescence by Activating the Superoxide Dismutase-Catalase Antioxidant Pathway and Down-Regulating Chlorophyll Degradation in Excised Leaves of Perennial Ryegrass (Lolium perenne L.) - Zhang, Jing; Li, Huibin; Xu, Bin; Li, Jing; Huang, Bingru (Frontiers in Plant Science, 2016)
Leaf senescence is a typical symptom in plants exposed to dark and may be regulated by plant growth regulators. The objective of this study was to determine whether exogenous application of melatonin (N-acetyl-5-methoxytryptamine) suppresses dark-induced leaf senescence and the effects of melatonin on reactive oxygen species (ROS) scavenging system and chlorophyll degradation pathway in perennial grass species. Mature perennial ryegrass (Lolium perenne L. cv. ‘Pinnacle’) leaves were excised and incubated in 3 mM 2-(N-morpholino) ethanesulfonic buffer (pH 5.8) supplemented with melatonin or water (control) and exposed to dark treatment for 8 d. Leaves treated with melatonin maintained significantly higher endogenous melatonin level, chlorophyll content, photochemical efficiency, and cell membrane stability expressed by lower electrolyte leakage and malondialdehyde (MDA) content compared to the control. Exogenous melatonin treatment also reduced the transcript level of chlorophyll degradation-associated genes and senescence marker genes (LpSAG12.1, Lph36, and Lpl69) during the dark treatment. The endogenous O2- production rate and H2O2 content were significantly lower in these excised leaves treated with melatonin compared to the water control. Exogenous melatonin treatment caused increases in enzymatic activity and transcript levels of superoxide dismutase and catalase but had no significant effects on ascorbate peroxidase, glutathione reductase, dehydroascorbate reductase, and monohydroascorbate reductase. The content of non-enzymatic antioxidants, such as ascorbate and dehydroascorbate, were decreased by melatonin treatment, while the content of glutathione and oxidized glutathione was not affected by melatonin. These results suggest that the suppression of dark-induced leaf senescence by exogenous melatonin may be associated with its roles in regulating ROS scavenging through activating the superoxide dismutase-catalase enzymatic antioxidant pathway and down-regulating chlorophyll degradation in perennial ryegrass.